Advances in RNA-Based Therapeutics: Challenges and Innovations in RNA Delivery Systems - Yuxuan Liu; Yaohui Ou; Linlin Hou (Current Issues in Molecular Biology)
Nucleic acids, as carriers of genetic information, have found wide applications in both medical and research fields, including gene editing, disease diagnostics, and drug development. Among various types of nucleic acids, RNA offers greater versatility compared to DNA due to its single-stranded structure, ability to directly encode proteins, and high modifiability for targeted therapeutic and regulatory applications. Despite its promising potential in biomedicine, RNA-based medicine still faces several challenges. Notably, one of the most significant technical hurdles is achieving efficient and targeted RNA delivery while minimizing immune responses. Various strategies have been developed for RNA delivery, including viral vectors, virus-like particles (VLPs), lipid nanoparticles (LNPs), and extracellular vesicles (EVs). In this review, we explore the applications of these delivery methods, highlight their advantages and limitations, and discuss recent research advancements, providing insights for the future of RNA-based therapeutics.